In ‘other’ words: Some thoughts on the transferability of collocations - Odlin, Terence (Studies in Second Language Learning and Teaching, 2011)
In discussions of cross-linguistic influence (also known as language transfer), the focus is usually on the influence of a particular structure in a particular instance of language contact, for instance, the negative transfer of serial verbs by Vietnamese learners of English: She has managed to rise the kite fly over the tallest building (Helms-Park, 2003). Even so, as Helms-Park acknowledges, serial verb constructions can and do surface in contact situations besides the one she studied in Canada, and they can involve speakers of different languages. While serial verb constructions have unique syntactic traits, the same point about the transferability of multiword constructions in different contact settings is applicable in other instances and with collocations that can be viewed as unique in their lexical as well as syntactic characteristics. The following article considers such a case, based in part on my own teaching experience but also on transfer research from other settings as well. After a discussion of a collocation that I call the repeated other pattern found in different settings, I briefly consider other cases of transfer having lexical and syntactic peculiarities and appearing in more than one contact situation. There will also be some discussion of factors that transfer researchers and language teachers would do well to consider.